Haemodynamic effects of hyperventilation on healthy men with different levels of autonomic tone - V. A. Zavhorodnia; O. I. Androshchuk; T. H. Kharchenko; L. I. Kudii; S. O. Kovalenko (Regulatory Mechanisms in Biosystems, 2020)
The topicality of the research is stipulated by insufficient study of the correlation between the functional state of the cardiorespiratory system and autonomic tone. The goal of the research was to analyze the changes of central haemodynamics with 10-minute regulated breathing at the rate of 30 cycles per minute and within 40 minutes of recovery after the test in healthy young men with different levels of autonomic tone. Records of the chest rheoplethysmogram were recorded on a rheograph KhAI-medica standard (KhAI-medica, Kharkiv, Ukraine), a capnogram - in a lateral flow on a infrared capnograph (Datex, Finland), and the duration of R-R intervals was determined by a Polar WIND Link in the program of Polar Protrainer 5.0 (Polar Electro OY, Finland). Systolic and diastolic blood pressure were measured by Korotkov’s auscultatory method by mercury tonometer (Riester, Germany). The indicator of the normalized power of the spectrum in the range of 0.15–0.40 Hz was evaluated by 5-minute records; three groups of persons were distinguished according to its distribution at rest by the method of signal deviation, namely, sympathicotonic, normotonic and parasympathicotonic. The initial level of autonomic tone was found to impact the dynamics of СО2 level in alveolar air during hyperventilation and during recovery thereafter. Thus, PetCО2 was higher (41.3 mm Hg) in parasympathicotonic than in sympathicotonic (39.3 mm Hg) and normotonic (39.5 mm Hg) persons. During the test, R-R interval duration decreased being more expressed in normotonic persons. At the same time, the heart index was found to increase in three groups, and general peripheral resistance – to decrease mostly in normo- and parasympathicotonic persons. In addition, the reliable increase of stroke index and heart index was found in these groups. In the recovery period after hyperventilation, the decrease of tension index and ejection speed was found in normo- and, particularly, parasympathicotonic compared with sympathicotonic men and the increase of tension phase and ejection phase duration.